Standard sample for pure zirconium glow mass spectrometry and preparation method and application thereof
Through vacuum electron beam smelting, vacuum consumable arc furnace smelting, reverse segregation treatment and induction coil smelting, the problem of segregation and uniform distribution of trace elements in standard samples was solved, and standard samples suitable for GDMS analysis were prepared, ensuring that The accuracy and traceability of the analysis results fill the domestic gap.
Patent Information
- Application Number
- CN202411470805.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-10
AI Technical Summary
In the existing pure zirconium glow mass spectrometry (GDMS) analysis methods, the segregation and uniform distribution of trace elements in standard samples are difficult to control, which affects the accuracy of the analysis results. There is a lack of standard samples suitable for GDMS analysis in China.
The sponge zirconium raw materials are processed by vacuum electron beam smelting, vacuum consumable electric arc furnace smelting, reverse segregation treatment and induction coil smelting. The uniform distribution of trace impurity elements is ensured through the pulling rod process, and a suitable for GDMS analysis is prepared. Standard sample.
Effectively control the segregation of trace impurity elements in pure zirconium, ensure the uniform distribution of elements in standard samples, improve the traceability system for pure zirconium glow mass spectrometry analysis, meet the analysis requirements of high-purity and ultra-high-purity metals, and fill the domestic Blank, suitable for ingredient analysis and quality control of pure zirconium products.
Smart Images

Figure CN119290525A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of analysis and detection, and in particular to a standard sample for pure zirconium glow mass spectrometry (GDMS) analysis and a preparation method and application thereof. Background Art
[0002] Zirconium is extremely stable at room temperature, resistant to radiation, corrosion, strong, and has excellent processing properties. Pure zirconium is obtained by purifying impurity elements on the basis of zirconium raw materials. It is widely used in industry, such as pressure vessels, heat exchangers, towers, agitators and other structural parts. The industry has strict requirements for the classification of pure metals, and its related test methods have extremely high requirements. At present, the main chemical analysis and testing methods for high-purity and ultra-pure metals are: inductively coupled plasma mass spectrometry (ICP-MS), glow discharge mass spectrometry (GDMS) and laser ablation-inductively coupled plasma mass spectrometry (LA-ICP-MS). Compared with ICP-MS liquid sampling and complex sample preparation process, LA-ICP-MS uses solid sampling, has a low detection limit, and is mainly used for the measurement of trace elements in minerals; GDMS uses solid direct sampling, with high sensitivity, low detection limit, and fast analysis speed. It is an ideal method for analyzing micro and trace impurity elements in high-purity and ultra-high-purity metals. GDMS is the only choice for the analysis of trace chemical components of pure metals, but the accuracy of the results of this analysis method depends on the corresponding standard samples. Therefore, the development of standard samples suitable for GDMS analysis is of great significance for ensuring the accurate analysis and control of the chemical components of high-purity and ultra-high-purity metals. How to prevent the segregation of trace elements in standard samples for GDMS analysis and make them evenly distributed is a technical problem that needs to be solved urgently. At present, no standard samples for pure zirconium glow mass spectrometry (GDMS) analysis have been found in China. Summary of the invention
[0003] In view of this, one purpose of the present application is to provide a method for preparing standard samples for pure zirconium glow mass spectrometry analysis. The sponge zirconium raw material is first melted by vacuum electron beam melting, vacuum consumable arc furnace melting, reverse segregation treatment and induction coil melting, and then the rod is drawn, which can ensure that the trace impurity elements in the prepared standard sample are evenly distributed, and thus the traceability system for pure zirconium glow mass spectrometry analysis can be improved.
[0004] Another object of the present application is to provide a standard sample for pure zirconium glow mass spectrometry analysis.
[0005] Yet another object of the present application relates to the application of standard samples for pure zirconium glow mass spectrometry analysis.
[0006] To achieve the above object, the first aspect of the present application proposes a method for preparing a standard sample for pure zirconium glow mass spectrometry analysis, comprising:
[0007] The sponge zirconium raw material is subjected to vacuum electron beam melting and vacuum consumable melting to obtain an ingot; the sponge zirconium raw material includes impurity elements;
[0008] The ingot is subjected to a reverse segregation treatment to obtain a rod bundle;
[0009] The rod bundle is sequentially subjected to induction coil melting and rod drawing to obtain a pure zirconium rod blank;
[0010] After the pure zirconium rod blank is subjected to surface treatment, cutting and testing to be qualified, the standard sample for the pure zirconium glow mass spectrometry analysis is obtained.
[0011] In some embodiments, the ingot has a first end, a middle portion, and a second end arranged in sequence along the height direction, the impurity element content of the first end is greater than the impurity element content of the middle portion, and the impurity element content of the middle portion is greater than the impurity element content of the second end.
[0012] In some embodiments, along a cross section perpendicular to the height direction of the ingot, the impurity element content at the center of the ingot is greater than the impurity element content at the edge of the ingot.
[0013] In some embodiments, the ingot includes a first end face and a second end face that are parallel to each other, and the ingot is subjected to a reverse segregation treatment, comprising:
[0014] The ingot is cut along a first direction and a second direction respectively to form a plurality of first long rods; the second direction is arranged perpendicular to the first direction, and there are multiple cutting positions in the second direction;
[0015] Welding the end faces corresponding to the first end face and the second end face on two first long bars on the same center line between the first end face and the second end face to form a plurality of second long bars;
[0016] The plurality of the second long rods are reassembled and welded in a manner that the center and the edge of the cross section of the original ingot are reversed to obtain the rod bundle.
[0017] In some embodiments, the cutting position in the first direction is located in the middle of the ingot.
[0018] In some embodiments, the cutting position in the first direction is arranged parallel to the first end surface and the second end surface of the ingot;
[0019] In some embodiments, the cutting in the second direction comprises multiple transverse cuttings and multiple longitudinal cuttings.
[0020] In some embodiments, the length and width of the cross section of the first long rod parallel to the first end surface are both 30-40 mm.
[0021] In some embodiments, the ingot is in the shape of a cylinder.
[0022] In some embodiments, the rod bundle is in the shape of a cylinder, a cuboid, a cube, or a special shape.
[0023] In some embodiments, the impurity elements include at least one of Ni, W, Mn, Sn, Al, Cr, Fe and Hf, and the mass contents of Ni, W, Mn and Sn in the sponge zirconium raw material are all 0.00001-0.0040%, and / or the mass contents of Al, Cr, Fe and Hf in the sponge zirconium raw material are all 0.0010-0.0500%.
[0024] In some embodiments, the induction coil smelting comprises:
[0025] Under vacuum conditions, performing a first smelting on the ingot at a first power;
[0026] After the pure zirconium in the ingot begins to melt, a second smelting is performed at a second power;
[0027] The first power is greater than the second power.
[0028] In some embodiments, the vacuum degree of the vacuum condition is 1.0×10 -2 Pa to 1.0×10 -3 Pa.
[0029] In some embodiments, the power of the first smelting is 100-110 KW.
[0030] In some embodiments, the power of the second smelting is 50-70 KW.
[0031] In some embodiments, after the ingot is melted by the induction coil, the mass of the molten metal is 25-35% of the mass of the ingot.
[0032] In some embodiments, the power when pulling the rod is 35-45KW.
[0033] In some embodiments, the rod pulling rate is 2-3 mm / min.
[0034] In some embodiments, the pure zirconium rod blank has a diameter of 30-42 mm and a height of 800-1000 mm.
[0035] In some embodiments, the detection includes uniformity detection, stability detection and value determination.
[0036] In some embodiments, the ingot has a diameter of 70-110 mm.
[0037] In some embodiments, the height of the ingot is 100-130 mm.
[0038] The second aspect of the present application proposes a standard sample for pure zirconium glow mass spectrometry analysis, which is prepared using the preparation method of the standard sample for pure zirconium glow mass spectrometry analysis of the present application.
[0039] The third aspect of the present application relates to the application of the standard sample for pure zirconium glow mass spectrometry analysis in the present application in glow discharge mass spectrometry analysis.
[0040] The method for preparing a standard sample for pure zirconium glow mass spectrometry analysis described in this application can at least bring the following beneficial effects:
[0041] 1. The sponge zirconium raw material is first melted by vacuum electron beam melting, vacuum consumable arc furnace melting, reverse segregation treatment and induction coil melting, and then the rod is drawn, which can effectively control the segregation of trace impurity elements in pure zirconium and ensure the uniform distribution of trace impurity elements in the prepared standard sample, thereby improving the pure zirconium glow mass spectrometry analysis traceability system.
[0042] 2. The composition design of standard samples for pure zirconium glow mass spectrometry (GDMS) analysis can meet the analysis requirements of hafnium sponge, hafnium rods, hafnium wires and hafnium plates.
[0043] 3. After uniformity inspection and stability test, as well as collaborative determination by 8 qualified laboratories using two principle analysis methods, it meets the requirements of standard samples.
[0044] 4. The comparison results show that the pure zirconium glow mass spectrometry (GDMS) standard sample prepared in this application fills the domestic gap.
[0045] 5. The standard sample for pure zirconium glow mass spectrometry analysis of the present application can be used for the calibration of pure zirconium glow mass spectrometry (GDMS) quality control detection instruments.
[0046] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings.
[0048] in:
[0049] Figure 1 The present invention is a flowchart of a method for preparing a standard sample for pure zirconium glow mass spectrometry analysis, showing an exemplary embodiment of the present application.
[0050] Figure 2 The present invention is a flow chart of reverse segregation treatment in a method for preparing a standard sample for pure zirconium glow mass spectrometry analysis according to an exemplary embodiment of the present application.
[0051] Figure 3a for Figure 2 Schematic diagram of the structure of the ingot, where the oo line represents the center line of the ingot, a represents the center of the ingot, a is on the oo line, and b represents the edge of the ingot.
[0052] Figure 3b for Figure 2 A diagram of the state of the ingot after being cut along the first direction (i.e., the circumferential direction).
[0053] Figure 3c for Figure 2 The state diagram after cutting along the second direction (i.e. axial direction) of the ingot.
[0054] Figure 3d for Figure 2 A structural diagram of two first long rods located on a common center line between a first end face and a second end face formed after the middle ingot is cut in a first direction and a second direction, wherein the two first long rods located on a common center line between the first end face and the second end face refer to, for example Figure 3d The two first long rods shown in a' and b' are coaxially arranged up and down.
[0055] Figure 3e for Figure 2 A state diagram in which the head of one of the two first long rods having a common center line between the first end face and the second end face is welded together with the bottom of the other one to form a second long rod.
[0056] Figure 3f for Figure 2 A state diagram of a rod bundle obtained by recombining and welding a plurality of second long rods in a manner of inverting the center and the edge of the cross section of the original ingot.
[0057] Figure 3g for Figure 3f Schematic diagram of the rod bundle combination rule, where b represents the original ingot ( Figure 1 The edge of the ingot in the rod bundle is at the center of the rod bundle, and a represents the original ingot ( Figure 1 The center part of the ingot in the rod bundle is at the edge of the rod bundle.
[0058] Reference numerals:
[0059] 1-first end face; 2-second end face; 3-cutting position in the first direction; 4-first part; 5-second part; 6-cutting position in the second direction; 7-first long rod; 700-middle part; 701-head; 702-bottom; 8-weld; 9-second long rod. DETAILED DESCRIPTION
[0060] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.
[0061] In this application, the disclosure of numerical ranges includes all values within the entire range and the disclosure of further subdivided ranges, including the endpoints and sub-ranges given in these ranges.
[0062] In this application, the raw materials, equipment, etc. involved, unless otherwise specified, are all raw materials and equipment that can be made through commercial channels or known methods; the methods involved, unless otherwise specified, are all conventional methods.
[0063] The inventors have found that glow discharge mass spectrometry (GDMS) uses a solid direct sampling method with high sensitivity, low detection limit and fast analysis speed, and is an ideal method for analyzing trace impurity elements in high-purity and ultra-high-purity metals. However, the accuracy of the results of this analysis method needs to rely on corresponding standard samples to ensure that the trace elements in the standard samples used for GDMS analysis are uniformly distributed, and how to prevent the segregation of trace elements in the standard samples used for GDMS analysis is a technical problem that needs to be solved urgently.
[0064] In order to solve the problem of uniform control of trace elements in standard samples for GDMS analysis and effectively prepare standard samples of glow mass spectrometry with uniform distribution of multiple trace elements, the inventors have found that the above goals can be achieved by using trace element uniform melting technology and uniform processing one-step molding technology.
[0065] Specifically:
[0066] Uniform melting technology of trace impurity elements: vacuum electron beam melting + vacuum consumable arc furnace melting + reverse segregation preparation method + induction coil melting. Vacuum electron beam melting is a melting method with the best purification effect in industrial production. The impurity elements Ni, Mn, Sn, Al, Cr, and Fe elements concerned in this application have a saturated vapor pressure much greater than that of the base metal, and the content of the above impurity elements can be reduced by electron beam melting. W and Hf have a similar saturated vapor pressure to the base metal Zr, and their purification capacity in the electron beam is limited. The electron beam melting pool is shallow and the pool solidifies quickly, and impurity elements that are difficult to purify cannot be evenly distributed in the ingot. However, the vacuum consumable melting pool has a deeper depth and slow solidification. Combined with the stirring current, the impurity elements can be evenly distributed in the pool. Therefore, the metal zirconium purified by the electron beam furnace achieves most of the impurity element purification and content control, and then after vacuum consumable melting, impurity elements such as Ni, Mn, Sn, Al, Cr, Fe, W, and Hf can tend to be evenly distributed in the base metal. However, during the vacuum consumable arc melting process, each element has different balance coefficients (K values) due to its own characteristics, resulting in a certain segregation in the pure zirconium ingot. Although the content of each impurity element has been controlled after vacuum electron beam melting + vacuum consumable arc furnace melting, ppm-level segregation still exists, and the segregation shows the regularity of element content: the head is slightly higher in the axial direction, the middle is normal, the tail is slightly lower, and the center is slightly higher and the edge is slightly lower in the cross section. The reverse segregation preparation method is adopted: the ingot is cut into long bars with a cross section of (30-40) mm × (30-40) mm along the axial direction to achieve physical segmentation, mark the corresponding cross-sectional position, and then cut the long bar from the middle, and weld the two ends (head and tail) of the long bar together. Then the welded long bar is reassembled in a way that the center and edge of the original ingot cross section are reversed to form a new rod bundle, realizing the reverse segregation of the impurity element content distribution. The reverse segregated rod bundle is melted through an induction coil, and then redistributed through a segregation process. Combined with the dual effects of the induction coil and magnetic levitation stirring, the composition is completely uniform.
[0067] Uniform processing one-step forming technology: The molten metal melted by the induction coil is pulled into a rod and gradually solidified from the bottom to the top, reducing the upper and lower segregation of the molten pool, and forming it into a rod blank in one step, completely solving the problem of axial homogenization of the element solidification process.
[0068] The following describes a method for preparing a standard sample for pure zirconium glow mass spectrometry analysis according to an embodiment of the present application with reference to the accompanying drawings.
[0069] Figure 1 The present invention is a flowchart of a method for preparing a standard sample for pure zirconium glow mass spectrometry analysis, showing an exemplary embodiment of the present application.
[0070] like Figure 1 As shown, the standard sample preparation method for pure zirconium glow mass spectrometry analysis includes the following steps:
[0071] S101, subjecting the sponge zirconium raw material to vacuum electron beam melting and vacuum consumable melting to obtain an ingot.
[0072] In some embodiments, the zirconium sponge raw material includes impurity elements, and the impurity elements include at least one of Ni, W, Mn, Sn, Al, Cr, Fe and Hf.
[0073] In the examples of the present application, the mass content of each of the above impurity elements in the sponge zirconium raw material is a trace amount, generally not exceeding 0.05%.
[0074] As an optional example, the mass content of Ni, W, Mn and Sn in the sponge zirconium raw material is 0.00001-0.0040%, including but not limited to 0.00001%, 0.00005%, 0.0001%, 0.00015%, 0.00050%, 0.001%, 0.0015%, 0.002%, 0.0025%, 0.003%, 0.0035% or 0.0040%, etc. In the embodiment of the present application, the mass content of Ni, W, Mn and Sn in the sponge zirconium raw material is within the above range, which can ensure that the element requirements of the pure zirconium product in the prior art requirements are met, and it is convenient for the accurate determination of the developed standard sample. If it is lower than 0.00001%, the element content in the sponge zirconium is too low, and there is a purification effect in the smelting process, which causes the element content of the standard sample to decrease; at the same time, if the element content is too low, it cannot be accurately detected in the subsequent determination process, which will cause the determination failure.
[0075] As an optional example, the mass content of Al, Cr, Fe and Hf in the sponge zirconium raw material is 0.0010-0.0500%, including but not limited to 0.001%, 0.0015%, 0.002%, 0.0025%, 0.003%, 0.0035%, 0.0040%, 0.008%, 0.01%, 0.015%, 0.02%, 0.025%, 0.03%, 0.035%, 0.04%, 0.045% or 0.05%, etc.
[0076] In the embodiments of the present application, both vacuum electron beam melting and vacuum consumable melting can be performed using methods well known in the art.
[0077] In some embodiments, the shape of the ingot includes but is not limited to a cylinder (e.g. Figure 3a As shown), a rectangular parallelepiped or a cube, etc.
[0078] As an optional example, the shape of the ingot is cylindrical.
[0079] In some embodiments, the diameter of the ingot is 70-110 mm; the height of the ingot is 100-130 mm.
[0080] For example, the diameter of the ingot includes but is not limited to 70 mm, 80 mm, 90 mm, 100 mm or 110 mm.
[0081] Exemplarily, the height of the ingot includes but is not limited to 100 mm, 110 mm, 120 mm or 130 mm, etc.
[0082] In some embodiments, the ingot is formed along the height direction (e.g., Figure 3a A first end portion, a middle portion, and a second end portion are sequentially arranged between the first end face 1 and the second end face 2 (along the 00 line direction), the impurity element content of the first end portion is greater than the impurity element content of the middle portion, and the impurity element content of the middle portion is greater than the impurity element content of the second end portion.
[0083] It should be noted that, in the embodiments of the present application, the contents of all impurity elements conform to the above rules, except that in some cases, the contents of some impurity elements decrease more from the first end to the second end, while the contents of some impurity elements decrease less from the first end to the second end.
[0084] Exemplarily, the height of the middle portion is 45-55% of the overall height of the ingot, including but not limited to 45%, 48%, 51% or 55%.
[0085] Exemplarily, the first end includes a first end surface 1, the second end includes a second end surface 2, the first end and the second end are of equal height, and the first end, the middle portion, and the second end are continuously arranged.
[0086] In some embodiments, along a cross section perpendicular to the ingot height direction, the center of the ingot (e.g., Figure 3a The impurity element content at the edge of the ingot (e.g., Figure 3a The impurity element content at point b in the figure.
[0087] Exemplarily, the content of each impurity element gradually decreases from the center of the ingot to the edge of the ingot.
[0088] It should be noted that, in the embodiments of the present application, the contents of all impurity elements conform to the above rules, but in some cases, the contents of some impurity elements gradually decrease more from the center of the ingot to the edge of the ingot, and the contents of some impurity elements gradually decrease less from the center of the ingot to the edge of the ingot.
[0089] In some embodiments, the ingot includes a first end face 1 and a second end face 2 (eg, Figure 3a shown).
[0090] In some embodiments, the process conditions of vacuum electron beam melting are: melting current 12-30KA, voltage 10-25V, vacuum degree 0-8Pa.
[0091] Exemplarily, in the vacuum electron beam melting process, the melting current includes but is not limited to 12KA, 15KA, 20KA, 25KA, or 30KA, etc., the voltage includes but is not limited to 10V, 15V, 20V or 25V, etc., and the vacuum degree includes but is not limited to 0, 2.5Pa, 5Pa or 8Pa, etc.
[0092] In some embodiments, the process conditions for vacuum consumable arc furnace smelting are: smelting current 18-22KA, voltage 28-35V, vacuum degree 0-8Pa.
[0093] Exemplarily, in the vacuum consumable arc furnace melting process, the melting current includes but is not limited to 18KA, 19KA, 20KA, 21KA or 22KA, etc., the voltage includes but is not limited to 28V, 30V, 32V or 35V, etc., and the vacuum degree includes but is not limited to 0, 2.5Pa, 5Pa or 8Pa, etc.
[0094] S102, performing reverse segregation treatment on the ingot to obtain a rod bundle.
[0095] Figure 2 The present invention is a flow chart of reverse segregation treatment in a method for preparing a standard sample for pure zirconium glow mass spectrometry analysis according to an exemplary embodiment of the present application.
[0096] like Figure 2 , Figure 3a-3g As shown, the ingot is subjected to an inverse segregation treatment, comprising the following steps:
[0097] (1) The ingot is cut along a first direction and a second direction to form a plurality of first long rods 7; the second direction is perpendicular to the first direction, and there are multiple (more than 2) cutting positions 6 in the second direction.
[0098] (2) The end faces (i.e., the end faces corresponding to the first end face and the second end face) on the two first long rods on the same center line between the first end face and the second end face are Figure 3e The middle head 701 and the bottom 702 are welded to form a plurality of second long rods 9.
[0099] (3) According to the center of the original ingot cross section ( Figure 3a a in the middle) and the edge ( Figure 3a (b) The plurality of second long rods are reassembled and welded in an inverted manner to obtain a rod bundle.
[0100] It should be noted that in the embodiment of the present application, the cutting position along the first direction is based on the macroscopic distribution method of the impurity element content, and the specific position is not limited, as long as the ingot is cut along the first direction of the cutting position, and the two sides of the cutting position are butt-jointed to achieve the purpose of uniform impurity content above and below the original ingot. As a preferred method, the cutting position 3 in the first direction is located in the middle of the ingot.
[0101] In addition, for the convenience of welding and the consistency of the longitudinal characteristics of each first long rod, the cutting position 3 in the first direction is arranged parallel to the first end face 1 and the second end face 2 of the ingot.
[0102] In some embodiments, the ingot is cut along a first direction to form a first portion 4 and a second portion 5, and the first portion 4 and the second portion 5 have the same height. The first portion 4 includes a first end surface 1, and the second portion 5 includes a second end surface 2.
[0103] In some embodiments, the second cut comprises multiple transverse cuts and multiple longitudinal cuts.
[0104] It should be noted that in the embodiment of the present application, the order of cutting the ingot along the first direction and the cutting along the second direction is not limited, and the ingot may be first cut along the first direction to form the first part 4 and the second part 5 (such as Figure 3b ), and then cut along the second direction (as shown Figure 3c As shown) to form a plurality of first long rods 7 (as Figure 3c , 3d As shown), it can also be that the long rod is first cut along the second direction (the two first long rods with the same center line between the first end face and the second end face in step (2) are integrally formed, and the corresponding Figure 3d The head corresponding to 701 is the head of the long rod, and the bottom corresponding to 702 is the bottom of the long rod), and then cut along the first direction, at this time, a plurality of first long rods 7 (such as Figure 3c , 3d As shown, in step (2), the two first long rods 7 with a common center line between the first end face and the second end face each correspond to the head and the bottom of the aforementioned long rod, and the first direction cutting position is the middle part 700 of the long rod).
[0105] In the embodiment of the present application, a plurality of second long rods are reassembled in a manner that the center and edge of the cross section of the original ingot are reversed, wherein the center of the cross section of the original ingot is as follows: Figure 3a At a in the figure, the edge of the original ingot cross section is as follows Figure 3a At point b in the figure, since the element content at point a is greater than that at point b, in order to evenly distribute the elements, point b needs to be adjusted to the original point a, and point a needs to be adjusted to the original point b. The middle position of the line between a and b remains unchanged. The positions of the second long rods have been adjusted, and they are reassembled into a bundle and welded to obtain a rod bundle (such as Figure 3fand Figure 3g shown).
[0106] It should be noted that in the embodiments of the present application, Figure 3a Point a and point b in the figure do not only refer to the locations of point a and point b, but represent the areas within a certain interval (for example, 3-5 mm) around each of points a and point b. That is, point a is a cylinder centered on line oo (point a is on line oo), containing a first end face and a second end face and having the same height as the ingot; point b is a cylinder with a ring-shaped cross-section, which is within the certain interval from point b to point a, containing a first end face and a second end face and having the same height as the ingot.
[0107] In the embodiment of the present application, the end surfaces (i.e., the end surfaces corresponding to the first end surface and the second end surface) on the two first long rods on the same center line between the first end surface and the second end surface are Figure 3e The welding of the middle head 701 and the bottom 702 will form a weld 8.
[0108] As an optional example, the anti-segregation treatment of the embodiment of the present application includes: cutting the cylindrical ingot axially into long rods with a cross-section of (30~40)mm×(30~40)mm to achieve physical division and mark the corresponding cross-sectional position; then cutting the long rod from the middle and welding the two ends of the long rod together; finally, recombining the welded long rods in a manner that the center and edge parts of the original ingot cross-section are inverted to form a new rod bundle.
[0109] In some embodiments, the length and width of the cross section of the first long rod 701 parallel to the first end surface 1 are both 30-40 mm, including but not limited to 30 mm, 32 mm, 35 mm, 37 mm or 40 mm.
[0110] In some embodiments, the shape of the rod bundle includes but is not limited to a cylinder, a cuboid, a cube, a special shape (ie, the rod bundle is a special-shaped structure), and the like.
[0111] S103, performing induction coil melting and rod drawing on the rod bundle in sequence to obtain a pure zirconium rod blank.
[0112] In some embodiments, induction coil melting comprises the following steps:
[0113] Under vacuum conditions, the ingot is first melted at a first power; when the pure zirconium in the ingot begins to melt, the ingot is second melted at a second power; the first power is greater than the second power.
[0114] In some embodiments, the vacuum degree of the vacuum condition is 1.0×10 -2 Pa to 1.0×10 -3 Pa, including but not limited to 1.0×10 -3 Pa, 1.0×10-2 Pa, 5.0×10 -3 Pa, 7.0×10 -3 Pa or 9.0×10 -3 Pa et al.
[0115] In some embodiments, the power of the first smelting is 100-110 KW, including but not limited to 100 KW, 102.5 KW, 105 KW, 107.5 KW or 110 KW, etc.
[0116] In some embodiments, the power of the second smelting is 50-70 KW, including but not limited to 50 KW, 55 KW, 60 KW, 65 KW or 70 KW, etc.
[0117] In some embodiments, after the ingot is melted by the induction coil, the mass of the molten metal is 25-35% of the mass of the ingot, including but not limited to 25%, 27%, 30%, 32% or 35%, etc.
[0118] In some embodiments, the power when pulling the rod is 35-45 KW, including but not limited to 35 KW, 33 KW, 35 KW, 40 KW or 45 KW.
[0119] In some embodiments, the rod pulling rate is 2-3 mm / min, including but not limited to 2.2 mm / min, 2.3 mm / min, 2.5 mm / min, 2.8 mm / min or 3 mm / min.
[0120] In some embodiments, the diameter of the pure zirconium rod blank is 30-42 mm, including but not limited to 30 mm, 34 mm, 38 mm or 42 mm.
[0121] In some embodiments, the height of the pure zirconium rod blank is 800-1000 mm, including but not limited to 800 mm, 850 mm, 900 mm, 950 mm or 1000 mm.
[0122] S104, after surface treatment, cutting and testing of the pure zirconium rod blank, a standard sample for pure zirconium glow mass spectrometry analysis is obtained.
[0123] In some embodiments, the surface treatment method is turning.
[0124] In some embodiments, the cutting method is: cutting off the head and tail ends of the surface treated pure zirconium rod blank ( Figure 3g At the positions corresponding to the two ends 700), a sample with a length (or height) of 5mm to 8mm is obtained.
[0125] In some embodiments, the testing includes non-destructive testing, surface inspection, and chemical composition testing.
[0126] In the embodiments of the present application, non-destructive testing, surface testing and chemical composition testing are all technologies and methods known in the art and will not be described in detail here.
[0127] In some embodiments, the testing includes uniformity testing, stability testing, and calibration.
[0128] As an optional example, the test includes a uniformity test, a fixed value test and a stability test performed in sequence. Preferably, in order to save the process, when the uniformity test fails, it can be directly determined that the sample is not a standard sample without performing a fixed value test and a stability test.
[0129] The method for preparing a standard sample for pure zirconium glow mass spectrometry analysis according to the embodiment of the present application can at least bring the following beneficial effects:
[0130] 1. The sponge zirconium raw material is first melted by vacuum electron beam melting, vacuum consumable arc furnace melting, reverse segregation treatment and induction coil melting, and then the rod is drawn, which can effectively control the segregation of trace impurity elements in pure zirconium and ensure the uniform distribution of trace impurity elements in the prepared standard sample, thereby improving the pure zirconium glow mass spectrometry analysis traceability system.
[0131] 2. The composition design of standard samples for pure zirconium glow mass spectrometry (GDMS) analysis can meet the analysis requirements of hafnium sponge, hafnium rods, hafnium wires and hafnium plates.
[0132] 3. After uniformity inspection and stability test, as well as collaborative determination by 8 qualified laboratories using two principle analysis methods, it meets the requirements of standard samples.
[0133] 4. The comparison results show that the pure zirconium glow mass spectrometry (GDMS) standard sample prepared in the embodiment of the present application fills the domestic gap.
[0134] 5. The standard sample for pure zirconium glow mass spectrometry analysis in the embodiment of the present application can be used for calibration of pure zirconium glow mass spectrometry (GDMS) quality control detection instruments.
[0135] The standard sample for pure zirconium glow mass spectrometry analysis in the embodiment of the present application is prepared by the preparation method of the standard sample for pure zirconium glow mass spectrometry analysis in the embodiment of the present application.
[0136] The standard sample for pure zirconium glow mass spectrometry analysis in the embodiment of the present application can be used in glow discharge mass spectrometry analysis, for example, it can be used for calibration of pure zirconium glow mass spectrometry (GDMS) quality control detection instruments, etc.
[0137] Certain features of the present technology are further illustrated in the following non-limiting examples.
[0138] In the following embodiments and comparative examples, all elements in the zirconium sponge are uniformly distributed, wherein Ni, W, Mn, Sn, Al, Cr, Fe, and Hf are impurity elements.
[0139] Example 1
[0140] The method for preparing a standard sample for pure zirconium glow mass spectrometry analysis in this embodiment comprises the following steps:
[0141] Step 1: Select 200 kg of zirconium sponge having the composition shown in Table A.
[0142] Table A
[0143] element Ni W Mn Sn Al Cr Fe Hf Zr content, 0.0034 0.0009 0.0010 0.0032 0.0030 0.0035 0.0287 0.0037 99.52
[0144] Step 2: melt the zirconium sponge obtained in step 1 into an ingot by vacuum electron beam melting and vacuum consumable arc furnace melting.
[0145] The process conditions of vacuum electron beam melting are: melting current 16KA, voltage 17.5V, vacuum degree 4Pa;
[0146] The process conditions of vacuum consumable arc furnace melting are: melting current 20KA, voltage 31.5V, vacuum degree 4Pa;
[0147] The shape of the ingot is cylindrical with a diameter of 90 mm and a height of 130 mm.
[0148] Step 3: The ingot obtained in step 2 is treated on the surface to remove defects such as risers, oxide layers on the surface of the ingot, pores, etc., and then subjected to reverse segregation treatment to achieve reverse segregation of the ingot composition.
[0149] The surface treatment method is turning. After turning, the shape of the ingot is still a cylinder with a diameter of 80 mm, a height of 121 mm, and a surface roughness of 0.16 μm.
[0150] The method of reverse segregation treatment is: the surface treated ingot is cut axially into multiple long bars with a cross section of (30-40) mm × (30-40) mm or a similar size, to achieve physical segmentation, and the corresponding cross-sectional position is marked according to the inner and outer positions of the end surface. Then each long bar is cut from the middle to obtain two first long bars 7 of the same height. Then the two ends of each long bar (that is, the head 701 of one of the two first long bars 7 of the same height and the bottom 702 of the other) are butt-welded to obtain multiple second long bars 9. Then the multiple second long bars 9 are reassembled and welded in a manner that the center and edge parts of the original ingot cross section are reversed to form a rod bundle.
[0151] Step 4: insert the rod bundle after reverse segregation treatment obtained in step 2 into the crucible of the ingot pulling equipment, and evacuate the ingot pulling equipment. When the vacuum degree reaches 1.0×10 -3 Under Pa conditions, turn on the high-frequency power supply system of the ingot pulling equipment, adjust the power to 105KW, start induction coil heating and smelting, and after the pure zirconium begins to melt, the power quickly drops to about 58KW for continuous smelting. When the molten metal reaches a certain amount (the mass of the molten metal is 30% of the mass of the ingot), start pulling the rod under the linkage of the lower crucible plug, and then obtain the required cylindrical pure zirconium rod blank.
[0152] Among them, the power of the rod drawing is 40KW, the rod drawing rate is 2.5mm / min, and the rod drawing time is 320min; the diameter of the pure zirconium rod blank is 42mm and the height is 800mm.
[0153] Step 5: The pure zirconium rod blank obtained in step 4 is subjected to surface treatment, and the head, tail and outer surface layer are cut off, and the rod is cut into a fixed length (height is 6 mm), and then subjected to uniformity detection, fixed value detection and stability detection in sequence (when the uniformity detection shows that it is not suitable, the fixed value detection and stability detection may not be performed; when the fixed value is unqualified, the stability test may not be performed). The sample with qualified uniformity detection, fixed value detection and stability detection results is the standard sample for pure zirconium glow mass spectrometry analysis in this embodiment, and is marked as standard sample Zr-GD-6. Among them:
[0154] The surface treatment method is turning. After turning, the shape of the pure zirconium rod blank is a cylinder with a diameter of 40 mm, a height of 750 mm, and a surface roughness of 0.16 μm.
[0155] The method of uniformity detection is: take a 6mm high sheet sample from the head, middle and tail positions of the pure zirconium rod blank which has been surface treated in step 5 and cut off along the height direction of the pure zirconium rod blank, and mark them as sheet sample A, sheet sample B and sheet sample C respectively. Glow density mass spectrometry (GDMS) method is used to independently determine the impurity elements at the two ends and the middle of each sample along the diameter direction (respectively marked as point 1, point 2 and point 3), and a total of 9 points are taken from three pieces for uniformity inspection (GDMS detection is used for uniformity test (using the sensitivity factor (other metals) provided by the database), and all tests are based on the same calibration, which can be used to evaluate whether the results are uniform.), and the test results are shown in Table 1. The uniformity results are evaluated by variance method, and the specific evaluation method is: take the significance level as 0.05, the degrees of freedom V1=8, V2=18, and find F0.05=2.51 from the F test gold ring table.
[0156] If F<2.51, it is considered that there is no significant difference within and between groups, and the initial inspection is qualified.
[0157] If F≥2.51, it is considered that there are differences within and between groups and the initial inspection fails.
[0158] Table 1-1 Uniformity test results of Example 1
[0159]
[0160] According to Table 1-1, it can be seen from the variance method that the statistical values F of each impurity element in Example 1 are all less than 1.29, which is less than the critical F (2.51). There is no obvious difference within the group (between the points of the same sheet sample) and between the groups (between the same points of each sheet sample), and the uniformity test is qualified.
[0161] The method of determining the value is: send samples that have passed the composition uniformity inspection to 8 laboratories (qualified laboratories, with both industry representatives and regional representatives) for determination analysis. Through normality test, outlier test, precision test, calculate the arithmetic mean, single measurement standard deviation, standard value and expanded uncertainty of each group of data (refer to GB / T 15000 "Standard Sample Working Guide" and YS / T 409-2012 "Technical Specifications for Standard Samples for Nonferrous Metal Product Analysis"). The determination results of the Zr-GD-1 standard sample obtained in this embodiment are shown in Table 1-2.
[0162] Table 1-2 Results of Zr-GD-1 standard sample determination
[0163]
[0164]
[0165] The stability test method is: conduct a one-year follow-up test on the standard sample to ensure that the test conditions are basically consistent for multiple tests within one year, so that the difference in the results reflects the error caused by the standard sample itself. The deviation of the test results of the standard sample prepared in this embodiment at different times is less than the precision of the analysis method, so the standard sample can be considered stable. According to the stability of the published titanium alloy standard sample for at least ten years, the validity period of this standard sample can be determined to be ten years.
[0166] User Authentication:
[0167] The standard samples prepared in this example were sent to the National Titanium Material Inspection Center for testing. The test results are as follows:
[0168] A: The tested pure zirconium glow mass spectrometry (GDMS) standard sample has a reasonable composition design, good uniformity, and accurate and reliable fixed values.
[0169] B: This pure zirconium glow mass spectrometry (GDMS) standard sample is suitable for the composition analysis of pure zirconium ingots, pure zirconium bars, pure zirconium plates, and pure zirconium tubes, and has a good effect.
[0170] Example 2
[0171] This embodiment is basically the same as Embodiment 1, except that:
[0172] Step 1: Select 200 kg of zirconium sponge having the composition shown in Table B.
[0173] Table B
[0174]
[0175] The sample number of the standard sample prepared in this example is Zr-GD-2.
[0176] The uniformity test results are shown in Table 2-1.
[0177] Table 2-1 Uniformity test results of Example 2
[0178]
[0179]
[0180] According to Table 2-1, the variance method was used for evaluation. The statistical values F of each impurity element in Example 2 were all less than 1.47, which was less than the critical F (2.51). There was no significant difference within the group (between each point of the same sheet sample) and between groups (between the same points of each sheet sample), and the uniformity test was qualified.
[0181] The determination results of the Zr-GD-2 standard sample obtained in this example are shown in Table 2-2.
[0182] Table 2-2 Results of Zr-GD-2 standard sample determination
[0183]
[0184] The stability test method is: conduct a one-year follow-up test on the standard sample to ensure that the test conditions are basically consistent for multiple tests within one year, so that the difference in the results reflects the error caused by the standard sample itself. The deviation of the test results of the standard sample prepared in this embodiment at different times is less than the precision of the analysis method, so the standard sample can be considered stable. According to the stability of the published titanium alloy standard sample for at least ten years, the validity period of this standard sample can be determined to be ten years.
[0185] User Authentication:
[0186] The standard samples prepared in this example were sent to the National Titanium Material Inspection Center for testing. The test results are as follows:
[0187] A: The tested pure zirconium glow mass spectrometry (GDMS) standard sample has a reasonable composition design, good uniformity, and accurate and reliable fixed values.
[0188] B: This pure zirconium glow mass spectrometry (GDMS) standard sample is suitable for the composition analysis of pure zirconium ingots, pure zirconium bars, pure zirconium plates, and pure zirconium tubes, and has a good effect.
[0189] Example 3
[0190] This embodiment is basically the same as Embodiment 1, except that:
[0191] Step 1: Select 200 kg of zirconium sponge having the composition shown in Table C.
[0192] Table C
[0193]
[0194] The sample number of the standard sample prepared in this example is Zr-GD-3.
[0195] The uniformity test results are shown in Table 3-1.
[0196] Table 3-1 Uniformity test results of Example 3
[0197]
[0198]
[0199] According to Table 3-1, the variance method was used for evaluation. The statistical values F of each impurity element in Example 3 were all less than 1.22, which was less than the critical F (2.51). There was no significant difference within the group (between each point of the same sheet sample) and between groups (between the same points of each sheet sample). The uniformity test was qualified.
[0200] The results of the Zr-GD-3 standard sample determination obtained in this example are shown in Table 3-2.
[0201] Table 3-2 Results of determination of Zr-GD-3 standard samples
[0202]
[0203] The stability test method is: conduct a one-year follow-up test on the standard sample to ensure that the test conditions are basically the same for multiple tests within one year, so that the difference in the results reflects the error caused by the standard sample itself. The deviation of the test results of the standard sample prepared in this embodiment at different times is less than the precision of the analysis method, so it can be considered that the standard sample is stable. According to the stability of the published titanium alloy standard sample for at least ten years, the validity period of this standard sample can be determined to be ten years.
[0204] User Authentication:
[0205] The standard samples prepared in this example were sent to the National Titanium Material Inspection Center for testing. The test results are as follows:
[0206] A: The tested pure zirconium glow mass spectrometry (GDMS) standard sample has a reasonable composition design, good uniformity, and accurate and reliable fixed values.
[0207] B: This pure zirconium glow mass spectrometry (GDMS) standard sample is suitable for the composition analysis of pure zirconium ingots, pure zirconium bars, pure zirconium plates, and pure zirconium tubes, and has a good effect.
[0208] Comparative Example 1 (without reverse segregation treatment step)
[0209] This comparative example is basically the same as Example 1, except that:
[0210] In step three, the ingot obtained in step two is surface treated without reverse segregation treatment, and in step four, the ingot surface treated in step three is directly placed in the crucible of the ingot pulling equipment.
[0211] The sample number of the sample prepared in this comparative example is Zr-GD-4.
[0212] The uniformity test results are shown in Table 4-1.
[0213] Table 4-1 Uniformity test results of comparative example 1
[0214]
[0215] According to Table 4-1, the variance method is used to evaluate that the statistical values F of each impurity element in Comparative Example 1 are all less than 1.67, which are greater than the critical F (2.51). There are obvious differences within the group (between the points of the same sheet sample) and between groups (between the same points of each sheet sample). The uniformity test fails. The sample does not meet the requirements of the standard sample and is not a standard sample.
[0216] Comparative Example 2
[0217] This comparative example is basically the same as Example 1, except that:
[0218] The second and third steps are not included, and in the fourth step, the zirconium sponge is directly placed into the crucible of the ingot pulling equipment.
[0219] The sample number of the sample prepared in this comparative example is Zr-GD-5.
[0220] The uniformity test results are shown in Table 5-1.
[0221] Table 5-1 Uniformity test results of comparative example 2
[0222]
[0223]
[0224] According to Table 5-1, the variance method is used to evaluate that the statistical values F of each impurity element in Comparative Example 2 are all less than 1.34, greater than the critical F (2.51), and there are obvious differences within the group (between the points of the same sheet sample) and between groups (between the same points of each sheet sample). The uniformity test fails, and the sample does not meet the requirements of the standard sample and is not a standard sample.
[0225] Comparative Example 3
[0226] This comparative example is basically the same as Example 1, except that:
[0227] Without step 3, step 4 is: forging the ingot obtained in step 2 into a Φ40mm pure zirconium bar blank.
[0228] The sample number of the sample prepared in this comparative example is Zr-GD-6.
[0229] The uniformity test results are shown in Table 6-1.
[0230] Table 6-1 Uniformity test results of comparative example 3
[0231]
[0232] According to Table 6-1, the variance method is used to evaluate that the statistical values F of each impurity element in Comparative Example 3 are all less than 1.71, greater than the critical F (2.51), and there are obvious differences within the group (between the points of the same sheet sample) and between groups (between the same points of each sheet sample). The uniformity test fails, and the sample does not meet the requirements of the standard sample and is not a standard sample.
[0233] In the present application, the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0234] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0235] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A method for preparing a standard sample for pure zirconium glow mass spectrometry analysis, characterized in that: include: The sponge zirconium raw material is subjected to vacuum electron beam melting and vacuum consumable melting to obtain an ingot; the sponge zirconium raw material includes impurity elements; The ingot is subjected to a reverse segregation treatment to obtain a rod bundle; The rod bundle is sequentially subjected to induction coil melting and rod drawing to obtain a pure zirconium rod blank; After the pure zirconium rod blank is subjected to surface treatment, cutting and testing to be qualified, the standard sample for the pure zirconium glow mass spectrometry analysis is obtained.
2. The preparation method according to claim 1, characterized in that: The ingot has a first end, a middle part and a second end arranged in sequence along the height direction, the impurity element content of the first end is greater than the impurity element content of the middle part, and the impurity element content of the middle part is greater than the impurity element content of the second end; and / or, In a cross section perpendicular to the height direction of the ingot, the content of the impurity elements in the center of the ingot is greater than the content of the impurity elements at the edge of the ingot.
3. The preparation method according to claim 1, characterized in that: The ingot comprises a first end face and a second end face which are parallel to each other, and the ingot is subjected to a reverse segregation treatment, comprising: The ingot is cut along a first direction and a second direction respectively to form a plurality of first long rods; the second direction is arranged perpendicular to the first direction, and there are multiple cutting positions in the second direction; Welding the end faces corresponding to the first end face and the second end face on two first long bars on the same center line between the first end face and the second end face to form a plurality of second long bars; The plurality of the second long rods are reassembled and welded in a manner that the center and the edge of the cross section of the original ingot are reversed to obtain the rod bundle.
4. The preparation method according to claim 3, wherein the cutting position in the first direction is located in the middle of the ingot; and / or, The cutting position in the first direction is arranged parallel to the first end face and the second end face of the ingot; and / or, The cutting in the second direction includes multiple transverse cutting and multiple longitudinal cutting; and / or, The length and width of the cross section of the first long rod parallel to the first end surface are both 30-40 mm; and / or, the ingot is in the shape of a cylinder; and / or, The rod bundle is in the shape of a cylinder, a cuboid, a cube or a special shape.
5. The preparation method according to claim 1, characterized in that: The impurity elements include at least one of Ni, W, Mn, Sn, Al, Cr, Fe and Hf, and the mass contents of Ni, W, Mn and Sn in the sponge zirconium raw material are all 0.00001-0.0040%, and / or the mass contents of Al, Cr, Fe and Hf in the sponge zirconium raw material are all 0.0010-0.0500%.
6. The preparation method according to claim 1, characterized in that: The induction coil melting comprises: Under vacuum conditions, performing a first smelting on the ingot at a first power; After the pure zirconium in the ingot begins to melt, a second smelting is performed at a second power; The first power is greater than the second power.
7. The preparation method according to claim 6, characterized in that: The vacuum degree of the vacuum condition is 1.0×10 -2 Pa to 1.0×10 -3 Pa; and / or, The power of the first smelting is 100-110KW; and / or, The power of the second smelting is 50-70KW.
8. The preparation method according to claim 1, characterized in that: After the ingot is melted by the induction coil, the mass of the molten metal is 25-35% of the mass of the ingot; and / or, The power of the rod pulling is 35-45KW; and / or, The rod pulling rate is 2-3 mm / min; and / or, The diameter of the pure zirconium rod blank is 30-42 mm and the height is 800-1000 mm; and / or, The detection includes uniformity detection, stability detection and setting value; and / or, The diameter of the ingot is 70-110 mm; and / or, The height of the ingot is 100-130 mm.
9. A standard sample for pure zirconium glow mass spectrometry analysis, characterized in that: The method is prepared according to any one of claims 1 to 8.
10. Use of the pure zirconium standard sample for glow mass spectrometry analysis as claimed in claim 9 in glow discharge mass spectrometry analysis.